Mycoviruses in Fusarium Species: An Update - Li, Pengfei; Bhattacharjee, Pallab; Wang, Shuangchao; Zhang, Lihang; Ahmed, Irfan; Guo, Lihua (Frontiers in Cellular and Infection Microbiology, 2019)
Fusarium is an important genus of plant pathogenic fungi, and is widely distributed in soil and associated with plants worldwide. The diversity of mycoviruses in Fusarium is increasing continuously due to the development and extensive use of state-of-the-art RNA deep sequencing techniques. To date, fully-sequenced mycoviruses have been reported in thirteen Fusarium species: Fusarium asiaticum, F. boothii, F. circinatum, F. coeruleum, F. globosum, F. graminearum, F. incarnatum, F. langsethiae, F. oxysporum, F. poae, F. pseudograminearum, F. solani, and F. virguliforme. Most Fusarium mycoviruses establish latent infections, but some mycoviruses such as Fusarium graminearum virus 1 (FgV1), Fusarium graminearum virus-ch9 (FgV-ch9), Fusarium graminearum hypovirus 2 (FgHV2), and Fusarium oxysporum f. sp. dianthi mycovirus 1 (FodV1) cause hypovirulence. Rapid advances in various omics technologies used to elucidate genes or biological processes can facilitate an improved understanding of mycovirus-host interactions. The review aims to illuminate the recent advances in studies of mycoviruses in Fusarium, including those related to diversity, molecular mechanisms of virus-host interaction. We also discuss the induction and suppression of RNA silencing including the role of RNAi components as an antiviral defense response.